Carbon fiber-based composite flexible heat-conducting cable and preparation method thereof
Patent Information
- Application Number
- CN202611078119.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-13
AI Technical Summary
然而,现有碳纤维基导热索技术仍存在不足:碳纤维的导热性能具有显著的各向异性,纤维间的热量传递效率较低,制约了整体导热性能的发挥;同时,碳纤维表面化学惰性较强,与金属接头的连接界面热阻较大,影响了热量从碳纤维主体向两端金属接头的有效传输;此外,已有方案的制备工艺较为繁琐,生产效率有待提高
本发明通过对碳纤维进行马来酸酐接枝改性并选用氨基化碳纳米管与之复配,酸酐基团与氨基之间的开环酰胺化反应能够在常规共混条件下高效进行,使碳纳米管以化学键合方式锚固于碳纤维表面,在纤维之间形成稳定的导热桥梁,这一机制有效改善了碳纤维径向导热能力差的固有缺陷。可碳化有机前驱体经高温碳化后转化为碳基体,填充于纤维与碳纳米管之间的空隙,进一步连通了导热路径。与现有技术中碳纤维与导热填料仅依靠物理混合的方案相比,化学键合网络赋予了导热索在反复弯折条件下更为稳定的导热性能。此外,可碳化前驱体以粉料形式直接混入浆料中,经一步热压即完成碳化与成型,避免了传统浸渍-碳化工艺中多次循环浸渍的繁琐操作,工艺更为简便,有利于规模化制备。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thermal conductive materials technology, specifically relating to a carbon fiber-based composite flexible thermal conductive cable and its preparation method. Background Technology
[0002] With the continuous increase in the integration and power density of electronic devices, and the stringent requirements for lightweight design and thermal control system reliability in aerospace equipment, efficient thermal management has become one of the key factors restricting system performance and service life. In spacecraft, satellites, and high-power electronic devices, there is often a certain spatial distance or relative movement between heat-generating components and heat sinks, making direct connection through rigid thermally conductive components difficult. Therefore, a thermally conductive connector with both high thermal conductivity and good flexibility, namely a heat-conducting cable, is needed to achieve heat transfer between the heat source and the heat sink.
[0003] Traditional heat-conducting cables are primarily made of metals such as copper and aluminum, constructed by connecting metal connectors at both ends of layers of metal braided strips or foils. While these metal heat-conducting cables offer stable thermal conductivity and mature connection technologies, their high metal density results in a heavy overall weight, making it difficult to meet the urgent lightweight requirements of spacecraft and portable electronic devices. Furthermore, in scenarios requiring long-distance heat transfer, the thermal resistance of metal heat-conducting cables increases significantly with length, limiting heat transfer efficiency. To address this issue, research has proposed flexible heat-conducting cable solutions based on graphite or graphene. However, while graphite and graphene-based heat-conducting cables possess extremely high in-plane thermal conductivity, their thermal conductivity in the thickness direction is weak. The interlayer bonding relies on van der Waals forces, making them prone to delamination under repeated bending or vibration, resulting in insufficient long-term reliability.
[0004] Carbon fiber possesses excellent axial thermal conductivity due to its highly oriented graphite microcrystalline structure along the fiber axis. It also boasts advantages such as low density, high strength, high modulus, and low coefficient of thermal expansion, making it an ideal material for constructing lightweight, flexible thermally conductive connectors. Researchers have already attempted to apply carbon fiber to the field of thermal conductive cables. For example, patent CN210725787U discloses a flexible thermally conductive strip and cable, which improves the thermal conductivity in the thickness direction by inserting carbon-based fibers into the stitching holes of a multilayer carbon-based thin film. Furthermore, patent CN113412026A proposes a method for preparing a lightweight, flexible carbon fiber / metal composite thermal conductive cable, which involves weaving carbon fiber bundles into a fabric and then combining it with a metal connector. However, existing carbon fiber-based heat-conducting cable technology still has shortcomings: the thermal conductivity of carbon fiber is significantly anisotropic, and the heat transfer efficiency between fibers is low, which restricts the overall thermal conductivity performance; at the same time, the surface of carbon fiber is chemically inert, and the thermal resistance at the interface with the metal joint is large, which affects the effective transfer of heat from the carbon fiber body to the metal joints at both ends; in addition, the existing preparation process is relatively complicated, and the production efficiency needs to be improved.
[0005] Therefore, there is an urgent need for a carbon fiber-based composite flexible heat-conducting cable and its preparation method that can fully utilize the axial thermal conductivity of carbon fiber and effectively improve the heat transfer efficiency between fibers. Summary of the Invention
[0006] This invention addresses the problems existing in the prior art by providing a carbon fiber-based composite flexible thermal conductive cable and its preparation method. The aim is to improve the thermal conductivity connection efficiency between fibers in the carbon fiber thermal conductive unit and reduce the interfacial thermal resistance between carbon fiber and metal joint through material composite and microstructure design, thereby obtaining a thermal conductive cable product that combines lightweight, flexibility and high thermal conductivity, meeting the application requirements of spacecraft thermal control systems and high-power electronic devices for efficient flexible thermal connection devices.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] The first aspect of the present invention provides a carbon fiber-based composite flexible heat-conducting cable, comprising: a strip-shaped flexible heat-conducting cable, and metal components respectively disposed at both ends of the flexible heat-conducting cable; The flexible heat-conducting tape is formed by stacking several carbon fiber heat-conducting units; The carbon fiber thermal conductive unit comprises the following components in parts by weight: 100 parts of maleic anhydride-grafted modified carbon fiber matrix; 5-12 parts of aminated carbon nanotubes; 10-20 parts of carbonizable organic precursor; Dispersing agent 2-4 parts.
[0009] Furthermore, the maleic anhydride-grafted modified carbon fiber matrix is prepared by a method comprising the following steps: (a) The carbon fiber matrix is immersed in a mixed solution containing AgNO3 and K2S2O8 and heated to obtain an oxidized carbon fiber matrix; (b) The oxidized carbon fiber matrix and maleic anhydride were added to an organic solvent and grafted under heating conditions via a Diels-Alder reaction to obtain a maleic anhydride grafted carbon fiber matrix.
[0010] Further, the concentration of AgNO3 in step (a) is 0.02 to 0.06 mol / L, and the concentration of K2S2O8 is 0.05 to 0.15 mol / L.
[0011] Further, the heating treatment in step (a) is performed at a temperature of 70–90°C for a time of 1–4 hours.
[0012] Further, in step (b), the mass ratio of the oxidized carbon fiber matrix to maleic anhydride is 1:1 to 1:3, the temperature of the Diels-Alder reaction is 140 to 180°C, and the reaction time is 4 to 10 hours.
[0013] Furthermore, the carbon fiber matrix is mesophase pitch-based carbon fiber or polyacrylonitrile-based carbon fiber, the thermal conductivity of the carbon fiber matrix is 300-800 W / (m·K), the fiber diameter is 5-15 μm, and the fiber length is 0.5-10 mm.
[0014] Furthermore, the amino content of the aminated carbon nanotubes is 0.3–2 wt%, the diameter is 5–20 nm, and the length is 1–30 μm.
[0015] Furthermore, the carbonizable organic precursor is any one of mesophase pitch, polyamic acid, or phenolic resin.
[0016] Furthermore, the dispersing agent is any one of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide, or polyvinylpyrrolidone.
[0017] Furthermore, the metal component is any one of copper, aluminum, copper alloy, or aluminum alloy, and the metal component is connected to the end of the flexible conductive tape by any one of welding, brazing, or pressing.
[0018] Furthermore, the fiber axis of the carbon fiber matrix is unidirectionally arranged along the length direction of the flexible conductive tape.
[0019] This invention introduces active reaction sites into the carbon fiber surface by chemically grafting maleic anhydride groups onto its surface. When aminated carbon nanotubes are blended with modified carbon fibers, the amino groups on the carbon nanotube surface undergo ring-opening amidation with the maleic anhydride groups on the carbon fiber surface, forming amide bonds and chemically anchoring the carbon nanotubes to the carbon fiber surface. Compared with the direct amidation reaction of carboxyl and amino groups, the ring-opening amidation reaction of anhydride groups with amino groups has higher reactivity and can be carried out efficiently under conventional blending conditions, which is beneficial for achieving sufficient interfacial bonding under the limited surface grafting density of carbon fibers. After this anchoring, the carbon nanotubes build thermally conductive bridges between fibers, effectively improving the inherent defect of poor radial thermal conductivity of carbon fibers. At the same time, the carbonizable organic precursor is transformed into a carbon matrix during high-temperature heat treatment, filling the gaps between carbon fibers and carbon nanotubes, ultimately forming a thermally conductive network with the synergistic effect of three mechanisms: thermal conductivity of the carbon fiber itself, thermal conductivity of the carbon nanotubes through bridging, and continuous thermal conductivity of the carbon matrix. This solves the problems of low interfiber heat transfer efficiency and high interfacial thermal resistance in traditional carbon fiber thermal cables.
[0020] A second aspect of this invention provides a method for preparing the above-mentioned carbon fiber-based composite flexible heat-conducting cable, comprising the following steps: (1) Weigh out the maleic anhydride-grafted modified carbon fiber matrix, aminated carbon nanotubes, carbonizable organic precursor and dispersant according to the ratio, add them to the dispersion medium and mix to obtain a mixed slurry; (2) The mixed slurry is formed into sheets or films and dried to obtain carbon fiber thermal conductive unit precursor; (3) After stacking 2 to 50 layers of carbon fiber thermal conductive unit precursor, hot pressing is performed in an inert atmosphere to carbonize the carbonizable organic precursor and bond the layers together to obtain a flexible thermal conductive material. (4) Connect the two ends of the flexible heat-conducting cable to the metal components respectively to obtain a carbon fiber-based composite flexible heat-conducting cable.
[0021] Further, the dispersion medium in step (1) is any one of water, N-methylpyrrolidone, dimethylformamide or anhydrous ethanol.
[0022] Further, the mixing in step (1) is any one or more combinations of mechanical stirring, ultrasonic dispersion or ball milling dispersion.
[0023] Furthermore, the molding described in step (2) is either casting molding or coating molding, and the carbon fiber matrix is oriented along the flow direction during the casting or coating process.
[0024] Furthermore, the hot pressing treatment in step (3) is a segmented heat treatment: first, it is treated at 800-1200℃ and 1-20MPa for 1-3 hours, and after the pressure is released, it is treated at 2000-2800℃ under normal pressure for 2-6 hours.
[0025] Compared with the prior art, the present invention has the following beneficial effects: This invention modifies carbon fibers by grafting maleic anhydride and then compounding them with aminated carbon nanotubes. The ring-opening amidation reaction between the anhydride groups and the amino groups can proceed efficiently under conventional blending conditions, anchoring the carbon nanotubes to the carbon fiber surface through chemical bonding. This forms stable thermally conductive bridges between the fibers, effectively improving the inherent defect of poor radial thermal conductivity in carbon fibers. The carbonizable organic precursor is transformed into a carbon matrix after high-temperature carbonization, filling the gaps between the fibers and carbon nanotubes, further connecting the thermal conduction pathways. Compared with existing technologies that rely solely on physical mixing of carbon fibers and thermally conductive fillers, the chemically bonded network endows the thermally conductive cables with more stable thermal conductivity under repeated bending conditions. Furthermore, the carbonizable precursor is directly mixed into the slurry in powder form, and carbonization and molding are completed in a single hot pressing step, avoiding the cumbersome operation of multiple impregnation cycles in the traditional impregnation-carbonization process. This simplifies the process and facilitates large-scale preparation. Detailed Implementation
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise specified, the raw materials used in the embodiments are all commercially available products.
[0027] Example 1 This embodiment provides a carbon fiber-based composite flexible heat-conducting cable, the preparation method of which includes the following steps: (1) Weigh the following raw materials according to the following mass percentages: 100 parts of maleic anhydride grafted modified carbon fiber matrix, 8 parts of aminated carbon nanotubes (amino content 1.2wt%, diameter 12nm, length 15μm), 14 parts of mesophase pitch, and 3 parts of sodium dodecylbenzenesulfonate. Add the above raw materials to 500 parts of N-methylpyrrolidone and mix for 2 hours by a combination of mechanical stirring and ultrasonic dispersion to obtain a uniform slurry.
[0028] (2) The mixed slurry is prepared into a sheet by casting. During the casting process, the slurry flows along the casting direction, and the carbon fiber matrix is oriented along the flow direction under the flow shear. The formed sheet blank is dried at 90°C for 8 hours to obtain the carbon fiber thermal conductive unit precursor.
[0029] (3) The 30-layer carbon fiber thermal conductive unit precursor is stacked in the same direction and placed in a hot press furnace. It is then subjected to segmented hot pressing under an argon atmosphere: first, it is treated at 1000℃ and 10MPa for 2 hours to carbonize the carbonizable organic precursor and bond the layers together; after the pressure is removed, the temperature is raised to 2400℃ and treated at normal pressure for 4 hours to perform graphitization treatment and obtain flexible thermal conductive material.
[0030] (4) The two ends of the flexible heat-conducting cable are connected to the copper metal component by brazing. The brazing temperature is 400℃ and the brazing time is 30min. The brazing is carried out under vacuum conditions to obtain carbon fiber-based composite flexible heat-conducting cable.
[0031] The maleic anhydride-grafted modified carbon fiber matrix was prepared according to the following method: (a) A mesophase pitch-based carbon fiber matrix (thermal conductivity of 500 W / (m·K), fiber diameter of 10 μm, and fiber length of 5 mm) was immersed in a mixed solution containing AgNO3 and K2S2O8, wherein the concentration of AgNO3 was 0.04 mol / L and the concentration of K2S2O8 was 0.10 mol / L, and the solution was heated at 80 °C for 2.5 h to obtain an oxidized carbon fiber matrix.
[0032] (b) The oxidized carbon fiber matrix and maleic anhydride were added to o-dichlorobenzene at a mass ratio of 1:2, and grafted at 160°C for 7 h via Diels-Alder reaction to obtain the maleic anhydride grafted carbon fiber matrix.
[0033] Example 2 This embodiment provides a carbon fiber-based composite flexible heat-conducting cable, the preparation method of which includes the following steps: (1) Weigh the following raw materials according to the following mass percentages: 100 parts of maleic anhydride grafted modified carbon fiber matrix, 5 parts of aminated carbon nanotubes, 20 parts of mesophase pitch, and 2 parts of sodium dodecylbenzenesulfonate. Add the above raw materials to 600 parts of N-methylpyrrolidone and mix for 2 hours by a combination of mechanical stirring and ultrasonic dispersion to obtain a uniform slurry.
[0034] (2) The mixed slurry is prepared into a sheet by casting. During the casting process, the slurry flows along the casting direction, and the carbon fiber matrix is oriented along the flow direction under the flow shear. The formed sheet blank is dried at 120°C for 6 hours to obtain the carbon fiber thermal conductive unit precursor.
[0035] (3) The 45-layer carbon fiber thermal conductive unit precursor is stacked in the same direction and placed in a hot press furnace. It is then subjected to segmented hot pressing under an argon atmosphere: first, it is treated at 900℃ and 15MPa for 1.5h to carbonize the carbonizable organic precursor and bond the layers together; after the pressure is removed, the temperature is raised to 2600℃ and treated at normal pressure for 5h to perform graphitization treatment to obtain the flexible thermal conductive material.
[0036] (4) The two ends of the flexible heat-conducting cable are connected to the copper metal component by brazing. The brazing temperature is 500℃ and the brazing time is 45min. The brazing is carried out under vacuum conditions to obtain carbon fiber-based composite flexible heat-conducting cable.
[0037] The carbon fiber matrix modified with maleic anhydride grafting was prepared according to the method in Example 1.
[0038] Example 3 This embodiment provides a carbon fiber-based composite flexible heat-conducting cable, the preparation method of which includes the following steps: (1) Weigh the following raw materials according to the following mass percentages: 100 parts of maleic anhydride grafted modified carbon fiber matrix, 12 parts of aminated carbon nanotubes, 10 parts of polyamic acid, and 4 parts of polyvinylpyrrolidone. Add the above raw materials to 400 parts of dimethylformamide and mix for 2 hours by a combination of mechanical stirring and ultrasonic dispersion to obtain a uniform slurry.
[0039] (2) The mixed slurry is prepared into a sheet by casting. During the casting process, the slurry flows along the casting direction, and the carbon fiber matrix is oriented along the flow direction under the flow shear. The formed sheet blank is dried at 70°C for 10 hours to obtain the carbon fiber thermal conductive unit precursor.
[0040] (3) The 15-layer carbon fiber thermal conductive unit precursor is stacked in the same direction and placed in a hot press furnace. It is then subjected to segmented hot pressing under an argon atmosphere: first, it is treated at 1100℃ and 5MPa for 2.5h to carbonize the carbonizable organic precursor and bond the layers together; after the pressure is removed, the temperature is raised to 2100℃ and treated at normal pressure for 3h to perform graphitization treatment to obtain the flexible thermal conductive material.
[0041] (4) The two ends of the flexible heat-conducting cable are respectively connected to the copper metal component by brazing. The brazing temperature is 300℃ and the brazing time is 50min. The brazing is carried out under vacuum conditions to obtain carbon fiber-based composite flexible heat-conducting cable.
[0042] The carbon fiber matrix modified with maleic anhydride grafting was prepared according to the method in Example 1.
[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that in step (1), the carbon fiber matrix modified by silane coupling agent grafting is used to replace the carbon fiber matrix modified by maleic anhydride grafting in an equal amount, while all other aspects are the same as in Example 1.
[0044] The silane coupling agent grafted modified carbon fiber matrix was prepared as follows: a mesophase pitch-based carbon fiber matrix (thermal conductivity of 500 W / (m·K), fiber diameter of 10 μm, and fiber length of 5 mm) was immersed in an ethanol / water solution containing silane coupling agent KH-550 (ethanol:water = 80:20, KH-550 mass fraction of 3%), the pH was adjusted to 3.5 with acetic acid, and the reaction was stirred at 70 °C for 4 h. After removal, it was repeatedly washed with anhydrous ethanol and deionized water, and vacuum dried at 60 °C for 12 h to obtain the silane coupling agent grafted modified carbon fiber matrix.
[0045] Comparative Example 2 The difference between this comparative example and Example 1 is that in step (1), the carbon fiber matrix modified by carboxylation is used to replace the carbon fiber matrix modified by maleic anhydride grafting in an equal amount, while all other steps are the same as in Example 1.
[0046] The carboxylated modified carbon fiber matrix was prepared as follows: the mesophase pitch-based carbon fiber matrix (thermal conductivity of 500 W / (m·K), fiber diameter of 10 μm, and fiber length of 5 mm) was immersed in 65% concentrated nitric acid and refluxed at 60 °C for 4 h. After removal, it was repeatedly washed with deionized water until the washing solution was neutral and vacuum dried at 60 °C for 12 h to obtain the carboxylated modified carbon fiber matrix.
[0047] Comparative Example 3 The difference between this comparative example and Example 1 is that the aminated carbon nanotubes in step (1) are replaced with unaminated original multi-walled carbon nanotubes in equal amounts, while all other aspects are the same as in Example 1.
[0048] Comparative Example 4 The difference between this comparative example and Example 1 is that the aminated carbon nanotubes in step (1) are replaced with hexagonal boron nitride in equal amounts, while all other aspects are the same as in Example 1.
[0049] Comparative Example 5 This comparative example provides a carbon fiber-based composite flexible heat-conducting cable, the preparation method of which includes the following steps: (1) Weigh the following raw materials according to the following mass percentages: 100 parts of maleic anhydride grafted modified carbon fiber matrix, 8 parts of aminated carbon nanotubes, and 3 parts of sodium dodecylbenzenesulfonate. Add the above raw materials to 500 parts of N-methylpyrrolidone and mix for 2 hours by a combination of mechanical stirring and ultrasonic dispersion to obtain a uniform slurry.
[0050] (2) The mixed slurry is prepared into a sheet by casting. During the casting process, the slurry flows along the casting direction, and the carbon fiber matrix is oriented along the flow direction under the flow shear. The formed sheet blank is dried at 90°C for 8 hours to obtain the carbon fiber thermal conductive unit precursor.
[0051] (3) The 30-layer carbon fiber thermal conductive unit precursor is stacked in the same direction and placed in a hot press furnace. It is treated at 1000℃ and normal pressure for 2 hours under argon atmosphere to pre-carbonize the sheet blank and obtain a porous carbon fiber preform.
[0052] (4) Dissolve the mesophase pitch in N-methylpyrrolidone to prepare an impregnation solution with a mass fraction of 30%. Immerse the porous carbon fiber preform obtained in step (3) into the impregnation solution and impregnate it under vacuum for 2 hours to allow the impregnation solution to fully penetrate the pores inside the preform.
[0053] (5) Take out the impregnated preform, dry it at 90°C for 8 hours, and then place it in a hot press furnace for carbonization treatment at 1000°C and normal pressure for 2 hours under argon atmosphere.
[0054] (6) Repeat the impregnation-carbonization operation of steps (4) and (5) twice (total impregnation-carbonization 3 times) to increase the filling density of the carbon matrix.
[0055] (7) The preform after three impregnation-carbonization processes is placed in a hot press furnace, heated to 2400℃ under argon atmosphere, and treated at normal pressure for 4 hours to obtain a flexible conductive tape.
[0056] (8) The two ends of the flexible heat-conducting cable are connected to the copper metal component by brazing. The brazing temperature is 400℃ and the brazing time is 30min. The brazing is carried out under vacuum conditions to obtain carbon fiber-based composite flexible heat-conducting cable.
[0057] The carbon fiber matrix modified with maleic anhydride grafting was prepared according to the method in Example 1.
[0058] Performance testing For each embodiment and comparative example, a sample of the flexible heat-conducting tape in the middle of the complete heat-conducting cable was taken and cut to a uniform size (50 mm in length, 10 mm in width, and the actual thickness of each embodiment / comparative example) for testing. Three parallel samples were taken for each test group, and the average value of the results was taken.
[0059] The testing method is as follows: 1. In-plane thermal conductivity: The thermal diffusivity α along the length direction (i.e., the fiber orientation direction) of the sample was measured using the laser flash method (referring to ASTM E1461 standard, selecting the in-plane test mode). The specific heat capacity Cp of the sample was determined by differential scanning calorimetry (DSC), and the density ρ was measured by the water displacement method. The in-plane thermal conductivity λ was calculated using the formula λ = α·Cp·ρ.
[0060] 2. Total Thermal Resistance: Tested according to ASTM D5470 standard using the steady-state heat flow method. The heat-conducting cable sample is clamped between the hot and cold ends, and a constant pressure of 0.5 MPa is applied. The heat flow rate Q through the sample and the temperature difference ΔT between the two sides of the sample are measured under steady-state conditions. The total thermal resistance R = ΔT·A / Q is calculated from the sample area A. The total thermal resistance is the sum of the sample's bulk thermal resistance and the contact thermal resistance at the interfaces on both sides.
[0061] 3. Thermal conductivity retention rate after bending: The thermal conductive cable sample is repeatedly bent around a cylinder with a diameter of 20mm 1000 times (bending angle 180°). The in-plane thermal conductivity is tested before and after bending using the laser flash method described above. The retention rate is calculated as: (In-plane thermal conductivity after bending / In-plane thermal conductivity before bending) × 100%.
[0062] The test results are shown in Table 1.
[0063] Table 1 Performance Test Results
[0064] The test results in Table 1 show that Examples 1-3 exhibit excellent in-plane thermal conductivity, total thermal resistance, and thermal conductivity retention after bending, indicating that the present invention effectively improves the thermal conductivity efficiency between fibers. Comparative Example 1 uses a silane coupling agent for modification; the coupling agent layer itself has poor thermal conductivity and limited bonding density, therefore its performance is lower than that of the examples. Comparative Example 2 uses carboxylation modification; the carboxyl and amino groups have low reactivity under conventional blending conditions, making it difficult to form sufficient interfacial bonds. Comparative Example 3 uses original carbon nanotubes; the surface lacks amino groups, making chemical bonding with anhydride groups impossible, and heat transfer relies solely on physical contact. Comparative Example 4 uses hexagonal boron nitride instead of carbon nanotubes; the contact mode between the sheet-like filler and the fiber is less efficient than the line-to-line contact of one-dimensional carbon nanotubes, and the surface also lacks reactive functional groups. Comparative Example 5 uses an impregnation-carbonization process; the precursor solution is limited by the uniform distribution of pores within the preform, resulting in uneven carbon matrix filling and less continuous thermal conductivity pathways compared to the slurry blending scheme.
[0065] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, and is not intended to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions made by those skilled in the art to the technical solution of the present invention do not depart from the essence and scope of the technical solution of the present invention.
Claims
1. A carbon fiber-based composite flexible heat-conducting cable, characterized in that, include: A strip-shaped flexible conductive tape, and metal components respectively disposed at both ends of the flexible conductive tape; The flexible heat-conducting tape is formed by stacking several carbon fiber heat-conducting units; The carbon fiber thermal conductive unit comprises the following components in parts by weight: 100 parts of maleic anhydride-grafted modified carbon fiber matrix; 5-12 parts of aminated carbon nanotubes; 10-20 parts of carbonizable organic precursor; Dispersing agent 2-4 parts.
2. The carbon fiber-based composite flexible heat-conducting cable according to claim 1, characterized in that, The maleic anhydride-grafted modified carbon fiber matrix is prepared by a method comprising the following steps: (1) The carbon fiber matrix is immersed in a mixed solution containing AgNO3 and K2S2O8 and heated to obtain an oxidized carbon fiber matrix; (2) The oxidized carbon fiber matrix and maleic anhydride were added to an organic solvent and grafted under heating conditions via Diels-Alder reaction to obtain a carbon fiber matrix grafted with maleic anhydride.
3. The carbon fiber-based composite flexible heat-conducting cable according to claim 2, characterized in that, The concentration of AgNO3 in step (1) is 0.02-0.06 mol / L, and the concentration of K2S2O8 is 0.05-0.15 mol / L; the temperature of the heating treatment is 70-90℃, and the time is 1-4h.
4. The carbon fiber-based composite flexible heat-conducting cable according to claim 2, characterized in that, In step (2), the mass ratio of the oxidized carbon fiber matrix to maleic anhydride is 1:1 to 1:3, the temperature of the Diels-Alder reaction is 140 to 180°C, and the reaction time is 4 to 10 hours.
5. The carbon fiber-based composite flexible heat-conducting cable according to claim 1, characterized in that, The carbon fiber matrix is mesophase pitch-based carbon fiber or polyacrylonitrile-based carbon fiber. The thermal conductivity of the carbon fiber matrix is 300-800 W / (m·K), the fiber diameter is 5-15 μm, and the fiber length is 0.5-10 mm. The amino content of the aminated carbon nanotubes is 0.3-2 wt%, the diameter is 5-20 nm, and the length is 1-30 μm.
6. The carbon fiber-based composite flexible heat-conducting cable according to claim 1, characterized in that, The carbonizable organic precursor is any one of mesophase pitch, polyamic acid, or phenolic resin; the dispersing agent is any one of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium bromide, or polyvinylpyrrolidone.
7. The carbon fiber-based composite flexible heat-conducting cable according to claim 1, characterized in that, The metal component is any one of copper, aluminum, copper alloy, or aluminum alloy, and the metal component is connected to the end of the flexible conductive tape by any one of welding, brazing, or pressing.
8. The carbon fiber-based composite flexible heat-conducting cable according to claim 1, characterized in that, The fibers of the carbon fiber matrix are unidirectionally arranged along the length of the flexible conductive tape.
9. The method for preparing the carbon fiber-based composite flexible heat-conducting cable according to any one of claims 1-8, characterized in that, Includes the following steps: (1) Weigh out the maleic anhydride-grafted modified carbon fiber matrix, aminated carbon nanotubes, carbonizable organic precursor and dispersant according to the ratio, add them to the dispersion medium and mix to obtain a mixed slurry; (2) The mixed slurry is formed into sheets or films and dried to obtain carbon fiber thermal conductive unit precursor; (3) After stacking 2 to 50 layers of carbon fiber thermal conductive unit precursor, hot pressing is performed in an inert atmosphere to carbonize the carbonizable organic precursor and bond the layers together to obtain a flexible thermal conductive material. (4) Connect the two ends of the flexible heat-conducting cable to the metal components respectively to obtain a carbon fiber-based composite flexible heat-conducting cable.
10. The preparation method according to claim 9, characterized in that, The molding described in step (2) is casting molding or coating molding, and the carbon fiber matrix is oriented along the flow direction during casting or coating; the hot pressing treatment described in step (3) is segmented heat treatment: first, it is treated at 800-1200℃ and 1-20MPa for 1-3 hours, and after the pressure is removed, it is treated at 2000-2800℃ under normal pressure for 2-6 hours.
Citation Information
Patent Citations
Preparation method of lightweight flexible carbon fiber / metal composite heat-conducting cable
CN113412026A
Flexible heat conduction strip and heat conduction cable
CN210725787U